Combating increased antifungal drug resistance in Cryptococcus, what should we do in the future? - Deng Hengyu; Song Jialin; Huang Yemei; Yang Chen; Zang Xuelei; Zhou Yangyu; Li Hongli; Dai Bin; Xue Xinying (Acta Biochimica et Biophysica Sinica, 2023)
Few therapeutic drugs and increased drug resistance have aggravated the current treatment difficulties of Cryptococcus in recent years. To better understand the antifungal drug resistance mechanism and treatment strategy of cryptococcosis. In this review, by combining the fundamental features of Cryptococcus reproduction leading to changes in its genome, we review recent research into the mechanism of four current anti-cryptococcal agents, coupled with new therapeutic strategies and the application of advanced technologies WGS and CRISPR-Cas9 in this field, hoping to provide a broad idea for the future clinical therapy of cryptococcosis.